Aplikasi Media Pembelajaran Untuk Meningkatkan Keterampilan Belajar Matematika Pada Anak Berbasis Multimedia - Suparno, Aknas Sukmawati; Udi Firmansyah, Ada (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
This study contributes to the development of multimedia-based teaching aids for mathematics education in kindergaeten. However, challenges arise with the discontinuation of support for Adobe Flash in 2020, which affects the accessibility of the application on modern devices. This study aims to design and develop an interactive multimedia teaching aid application for kindergarten children using the Multimedia Development Life Cycle (MDLC) development model. This application focuses on teachimg numbers, counting, and spatial structures through educational and interactive methods, development with Adobe Flash CS6. The data collection techniques used are observation, interviews, and literature studies to analyze the impact of media use on student motivation and understanding. The results of the study show that application is effective in increasing student learning motivation and facilitating understanding of basic mathematics material. Keywords: Learning Media, Adobe Flash CS6, MDLC, Mathematics.